The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3109/02713683.2012.697972
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Olfactory Ensheathing Cells Reduce Retinal Degeneration in Royal College of Surgeons Rats

Abstract: 2 AbstractPurpose of the study: Retinitis pigmentosa (RP) is a group of genetic disorders and a slow loss of vision is caused due to a cascade of retinal degenerative events. We examined whether these retinal degenerative events were relieved after the mixtures of cultured adult olfactory ensheathing cells (OECs) and olfactory nerve fibroblasts (ONFs) were transplanted into the subretinal space of one month old RCS rat, a classic model of RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Full-field ERGs were recorded after overnight dark adaptation as our previous protocol [39]. In brief, rats were anesthetized and the pupils were dilated with Compound Tropicamide Eye Drops.…”
Section: Methodsmentioning
confidence: 99%
“…Full-field ERGs were recorded after overnight dark adaptation as our previous protocol [39]. In brief, rats were anesthetized and the pupils were dilated with Compound Tropicamide Eye Drops.…”
Section: Methodsmentioning
confidence: 99%
“…In general, potential cells for retinal transplantation should have the following features: the ability to be easily cultured in vitro , the ability to migrate, the ability to differentiate into typical retinal cells and the ability to integrate into the retina 16 . According to this principle, the types of potential cells could be embryonic stem cells, human bone marrow derived mesenchymal stem cells (HBMSCs), neural stem cells, human retinal progenitor cells (HRPCs), olfactory unsheathing cells, Müller cells and adult photoreceptor or retina pigment cells 17–22 . All of these cells, which come from blastocysts, bone marrow, umbilical cord blood, adult forebrain or hippocampus, embryonic or neonatal retina, olfactory bulb and adult retina, have been used in transplanting potential cells into the subretinal space (SRS) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that the transplanted cells can be used as a substitute for degenerated cells or they can release some growth factors to enhance cell survival, growth and function of retinal cells. Transplanted cells types are: retinal pigment epithelium (RPE) [1], schwann cells [18], central nervous system stem cells [19], olfactory ensheathing cells [20], retinal stem cells [21], hematopoietic stem cells [22] and embryonic stem cells [23]. However, the clinical use of these cells have several problems, such as: limited availability of pluripotent retinal stem cells [24], and rejection by the host immune system in either allogeneic or xenogenic host species recipients [25], thus researchers prefer BMSCs for transplantation therapy.…”
Section: Introductionmentioning
confidence: 99%